Comparative Analysis and Modeling of Single and Three Phase Inverters for Efficient Renewable Energy Integration - Emon, Asif Eakball; Molla, Sohan; Shawon, Md; Tabassum, Anika (Scientific Journal of Engineering Research, 2025)
This work details the hands-on design, simulation, and direct performance comparison of single-phase and three-phase grid-connected photovoltaic (PV) inverters, fully implemented and tested within the MATLAB/Simulink environment. Moving beyond theoretical descriptions, we constructed detailed models incorporating practical elements: a PV array, a DC-DC boost converter with Perturb and Observe (P&O) Maximum Power Point Tracking (MPPT) for real-world energy harvesting, and both single-phase H-bridge and three-phase two-level voltage source inverters (VSIs) feeding the grid through carefully designed LCL filters. We subjected both systems to identical, realistic solar irradiance profiles and rigorously analyzed critical performance metrics side-by-side, including output waveform quality (Total Harmonic Distortion - THD), power conversion efficiency, DC-link voltage stability, and MPPT effectiveness. Our simulation results clearly demonstrate distinct operational characteristics: the three-phase inverter consistently delivered superior efficiency (approximately 97.8% vs. 96.5%), significantly lower output current THD (below 2.0% vs. approximately 3.8%), and reduced DC-link voltage ripple. Conversely, the single-phase topology offers inherent simplicity and lower cost for lower-power applications. This comparative analysis provides concrete, simulation-backed insights into the fundamental trade-offs between complexity, cost, efficiency, and power quality, directly informing the optimal selection of inverter technology—single-phase for standard residential use or three-phase for commercial/industrial systems demanding higher performance.